PERBANDINGAN HUKUM PENYELESAIAN SENGKETA SECARA MEDIASI DI PENGADILAN DAN DI LUAR PENGADILAN DI INDONESIA - Rika Lestari (Jurnal Ilmu Hukum, 2013)
Dispute resolution as mediationhas been known since the first inIndonesia because of the customssystem in resolving a case alwaysuphold discussion and consensusthrough traditional forums ofeach region in Indonesia. As itgrows by time, this is enforced inthe court (Court ConnectedMediation) as form of justice law.However, mediation process incourt has to be enforced throughthe civil dispute resolution. Ifmediation as set forth in SupremeCourt Rule No. 1 of 2008, ifmediation is not implemented, thejudgment will be omitted for lawpurpose.